2011
DOI: 10.1074/jbc.m111.238519
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Inflammasome-dependent Pyroptosis by Carbon Black Nanoparticles

Abstract: Inhalation of nanoparticles has been implicated in respiratory morbidity and mortality. In particular, carbon black nanoparticles are found in many different environmental exposures. Macrophages take up inhaled nanoparticles and respond via release of inflammatory mediators and in some cases cell death. Based on new data, we propose that exposure of macrophages (both a macrophage cell line and primary human alveolar macrophages) to carbon black nanoparticles induces pyroptosis, an inflammasome-dependent form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
103
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(111 citation statements)
references
References 72 publications
6
103
2
Order By: Relevance
“…15,16 Consistent with the hypothesis advanced by Darisipudi et al of an injurious role of inflammasome activation by uromodulin, toxin-induced pyroptosis may promote tissue injury, as shown for the lung. 15 However, the role of pyroptosis in kidney injury or in sterile inflammation has not been well characterized.…”
supporting
confidence: 70%
“…15,16 Consistent with the hypothesis advanced by Darisipudi et al of an injurious role of inflammasome activation by uromodulin, toxin-induced pyroptosis may promote tissue injury, as shown for the lung. 15 However, the role of pyroptosis in kidney injury or in sterile inflammation has not been well characterized.…”
supporting
confidence: 70%
“…Conversely to the NLRC-4 or the AIM-2, the NLRP-3 inflammasome is controlled by a priming step that requires de novo protein translation (35). Although carbon nanotubes and carbon black have also been reported to activate this inflam- masome in THP-1 and murine bone marrow-derived cells (20,46), the effect of AgNP on the inflammasome has never been reported. Herein, we show a cytotoxic and inflammatory role of AgNP 15 as evidenced by induction of pyroptotic cell death and IL-1␤ secretion.…”
Section: Discussionmentioning
confidence: 96%
“…The cell model has been applied to investigate NP-induced pulmonary toxicity and inflammasome activation. 45,46 This study has also shown that NiONPs induce active caspase-1 expression and IL-1β release in macrophages. Notably, knockdown of Nlrp3 completely abolishes caspase-1 activity and mature IL-1β release induced by NiONPs.…”
mentioning
confidence: 93%